2016
DOI: 10.1159/000452527
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of Erythrocyte Cell Membrane Scrambling by Emodin

Abstract: Background/Aims: The natural anthraquinone derivative emodin (1,3,8-trihydroxy-6-methylanthraquinone) is a component of several Chinese medicinal herbal preparations utilized for more than 2000 years. The substance has been used against diverse disorders including malignancy, inflammation and microbial infection. The substance is effective in part by triggering suicidal death or apoptosis. Similar to apoptosis of nucleated cells erythrocytes may enter suicidal erythrocyte death or eryptosis, characterized by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 132 publications
(55 reference statements)
1
21
0
Order By: Relevance
“…Overall, our studies further confirmed the anti-cancer effects of emodin and suggested that this agent can be used as potential therapeutic modality in several cancers [32, 33]. Although there were important discoveries revealed by previous studies indicated potential multiple signaling pathways and molecular genes or proteins that had been involved in the anti-tumor responses and other functions of emodin [8, 10, 34], the detailed molecular mechanisms by which this agent in anti-cancer effects still remained to be elucidated. Consistent with our previous study [11], we observed that emodin induced cell cycle arrest in G2/M phase checkpoint and reduced migration and invasion in lung cancer cells, which was in line with its widely established anti-tumor role of emodin [8-10, 35] implying the possibility of inhibition of both mitotic division and DNA replications which finally reduces cell division rates by emodin in this process.…”
Section: Discussionsupporting
confidence: 74%
“…Overall, our studies further confirmed the anti-cancer effects of emodin and suggested that this agent can be used as potential therapeutic modality in several cancers [32, 33]. Although there were important discoveries revealed by previous studies indicated potential multiple signaling pathways and molecular genes or proteins that had been involved in the anti-tumor responses and other functions of emodin [8, 10, 34], the detailed molecular mechanisms by which this agent in anti-cancer effects still remained to be elucidated. Consistent with our previous study [11], we observed that emodin induced cell cycle arrest in G2/M phase checkpoint and reduced migration and invasion in lung cancer cells, which was in line with its widely established anti-tumor role of emodin [8-10, 35] implying the possibility of inhibition of both mitotic division and DNA replications which finally reduces cell division rates by emodin in this process.…”
Section: Discussionsupporting
confidence: 74%
“…Intracellular accumulation of ROS was determined using fluorescent DCFH-DA [28, 29]. DCFH-DA is a stable, non-polar compound which readily diffuses into cells and is hydrolyzed by intracellular esterase to yield DCFH, which is trapped into the cells.…”
Section: Methodsmentioning
confidence: 99%
“…Enhanced eryptosis is observed in diverse clinical conditions including iron deficiency [58], vitamin D excess [117], chronic kidney disease (CKD) [118][119][120][121][122][123], hemolytic-uremic syndrome [124], autoimmune hemolytic anemia [125], diabetes [126], hypertension and dyslipidemia [127], hepatic failure [128], malignancy [129][130][131], arteritis [132], systemic lupus erythematosus [133], sepsis [134,135], malaria [58,136,137], sicklecell disease [58], beta-thalassemia [58], Hb-C and G6PD-deficiency [58], Wilsons disease [134], as well as advanced age [138]. Eryptosis further increases following storage for transfusion [67,68,83,139] and is enhanced in erythrocytes from newborns exposed to oxidative stress [58,140].…”
Section: Introductionmentioning
confidence: 99%